PRESERVATION OF FISH BY FREEZING AND GLAZING :III.EFFECT OF FREEZING ,GLAZING AND FROZEN STORAGE ON THE B- VITAMINS AND ESSENTIAL MINERALS PRESENT IN THE FISH FLESH. - JADHAV, M G; MAGAR, N G (Fishery Technology, 2025)
The changes occurring in moisture, thiamine, riboflavin niacin, phosphorus, iron and calcium in pomfrets, surmai and mackerel frozen, glazed with ascorbic acid. citric acid, sodium chloride & glucose and sodium nitrite and kept under frozen storage were studied upto 6 months and results reported.